2017
DOI: 10.1080/02713683.2017.1338350
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Central Retinal Artery Blood Flow Is Related to Impaired Central Visual Function in Retinitis Pigmentosa Patients

Abstract: Purpose We evaluated the test-retest repeatability of blood flow velocities in the retrobulbar central retinal artery (CRA) and explored whether reduced blood flow is related to the degree of visual function loss in retinitis pigmentosa (RP) patients with wide range of disease severity. Materials and Methods We measured CRA peak systolic velocity (PSV) and end diastolic velocity (EDV) to calculate mean flow velocity (MFV) in 18 RP patients using color Doppler imaging with spectral flow Doppler (GE Logiq7 ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Retrobulbar ocular hemodynamics in the CRA were measured with color Doppler imaging and spectral flow Doppler using the GE Logiq 7 according to previously published guidelines (Stalmans et al 2011) and procedures. (Kayser et al 2017) by trained sonographers (DM, PV, JH) who were masked to the subjects’ intervention group. Mean peak systolic velocity (PSV) and end diastolic velocity (EDV) were used to calculate mean flow velocity (MFV) using the equation: MFV=((PSV)+(2×EDV))/3.…”
Section: Methodsmentioning
confidence: 99%
“…Retrobulbar ocular hemodynamics in the CRA were measured with color Doppler imaging and spectral flow Doppler using the GE Logiq 7 according to previously published guidelines (Stalmans et al 2011) and procedures. (Kayser et al 2017) by trained sonographers (DM, PV, JH) who were masked to the subjects’ intervention group. Mean peak systolic velocity (PSV) and end diastolic velocity (EDV) were used to calculate mean flow velocity (MFV) using the equation: MFV=((PSV)+(2×EDV))/3.…”
Section: Methodsmentioning
confidence: 99%
“…Retinal circulation in eyes with macula-off RRD did not recover to the levels observed in fellow eyes until at least 6 months after 25G MIVS. Accumulating evidence suggests that retinal circulation is severely impaired in retinal degenerative diseases such as retinitis pigmentosa and other inherited retinal diseases 16 18 . Macula-off RRD led to thinning of the macula and degeneration of photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, reduced CRA blood flow was shown to be related to impaired central visual function in RP patients (Kayser et al. ). The authors concluded that reductions in CRA flow may occur prior to RP diagnosis or shortly thereafter, as impairment was present in RP subjects who had normal central visual function and greater than 4 years of self‐reported visual field loss (Kayser et al.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that reductions in CRA flow may occur prior to RP diagnosis or shortly thereafter, as impairment was present in RP subjects who had normal central visual function and greater than 4 years of self‐reported visual field loss (Kayser et al. ). These results indicate that vascular abnormalities in RP are not merely confined to the peripheral retina, but may also exacerbate the loss of central visual function.…”
Section: Methodsmentioning
confidence: 99%